Economic Performance in Latin America and the Caribbean : A Microeconomic Perspective, Volume 1. Main Findings - World Bank (Washington, DC, 2012)
Important findings of recent studies based on a macroeconomic perspective include the need to take actions aimed at further increasing the region's integration into the global economy while at the same time deepening Latin America's relatively shallow financial markets. This study complements that body of knowledge by taking an alternative microeconomic, firm-level approach to explain productivity and economic performance. In particular, instead of the usual cross country econometric methodologies used to uncover the determinants of per capita GDP growth, this study focuses on the analysis of the investment climate determinants of productivity and wages at the firm level. Six main findings emerge from this analysis: first, the governance agenda, encompassing the strengthening of the rule of the law and the improvement of institutions and regulatory frameworks, emerges as a key policy priority for improving firm performance in Latin America. Second, expanding access to credit also appears as a relevant policy priority. Third, innovation, technological development and human capital remain at the core of the agenda of reforms aimed at moving up in the value chain and securing the elusive goal of higher sustained growth. Fourth, the findings of this regional study complement the extensive evidence on the critical impact of infrastructure on growth and poverty. Fifth, the report shows that, after controlling for other factors, firms that export tend to perform better: they are more productive, pay higher wages and are more likely to innovate. And finally, benefits of an improved investment climate are not limited to firms, as their workers benefit significantly as well.